The effect of CAR on English language teachers’ beliefs about action research - Legesse, Ayele; Kitila, Tamene (Journal of Research on English and Language Learning (J-REaLL), 2024)
This study examined the effect of collaborative action research (CAR) on secondary school English language teachers' beliefs about and perceived competency in conducting action research. A quasi-experimental design with pre- and post-test measures within a single group was employed. The intervention involved a one-day training workshop followed by 15 months of active CAR engagement. Data were collected via questionnaires from 37 English language teachers (21 in the experimental group and 16 in the control group) at two secondary schools in Mettu town, Ethiopia. The results revealed a positive transformative effect of CAR on teachers’ beliefs about action research. Their perceived competency in conducting action research as part of their teaching duties also improved significantly. These findings suggest that CAR empowers teachers to become self-directed, collaborative problem solvers within their classrooms rather than passively waiting for external solutions. However, the study’s limitations, including its single-group design and focus on two schools, necessitate further research. Future studies, particularly in-depth qualitative investigations, are recommended to explore the practical changes in teaching practices driven by CAR and to diversify the subject group and research methods for broader insights.